Lepton universality in the νMSM - Takehiko Asaka; Shintaro Eijima; Kazuhiro Takeda (Physics Letters B, 2015)
We consider the νMSM which is an extension of the Standard Model by three right-handed neutrinos with masses below the electroweak scale, in which the origins of neutrino masses, dark matter, and baryon asymmetry of the universe are simultaneously explained. Among three heavy neutral leptons, N2 and N3, which are responsible to the seesaw mechanism of active neutrino masses and the baryogenesis via flavor oscillation, can induce sizable contributions to various lepton universality in decays of charged mesons. Then the possible deviations of the universality in the νMSM are investigated. We find that the deviation in kaon decay can be as large as O(10−3), which will be probed in near future experiments.